Risks, Benefits, and Treatment Modalities of Menopausal Hormone Therapy: Current Concepts - Mehta, Jaya; Kling, Juliana M.; Manson, JoAnn E. (Frontiers in Endocrinology, 2021)
Menopausal hormone therapy (HT) prescribing practices have evolved over the last few decades guided by the changing understanding of the treatment’s risks and benefits. Since the Women’s Health Initiative (WHI) trial results in 2002, including post-intervention analysis and cumulative 18-year follow up, it has become clear that the risks of HT are low for healthy women less than age 60 or within ten years from menopause. For those who are experiencing bothersome vasomotor symptoms, the benefits are likely to outweigh the risks in view of HT’s efficacy for symptom management. HT also has a role in preventing osteoporosis in appropriate candidates for treatment. A comprehensive overview of the types, routes, and formulations of currently available HT, as well as HT’s benefits and risks by outcomes of interest are provided to facilitate clinical decision making.